Deficits in verbal fluency in presymptomatic C9orf72 mutation gene carriers: a developmental disorder - Lulé, Dorothée; Müller, Hans-Peter; Finsel, Julia; Weydt, Patrick; Knehr, Antje; Winroth, Ivar; Andersen, Peter; Weishaupt, Jochen H.; Uttner, Ingo; Kassubek, Jan Rainer; Ludolph, Albert C. (Journal of neurology, neurosurgery, and psychiatry, 2020)
Background A mutation in C9orf72 constitute a cross-link between amyotrophic lateral sclerosis (ALS) and fronto-temporal dementia (FTD). At clinical manifestation, both patient groups may present with either cognitive impairment of predominantly behaviour or language (in FTD) or motor dysfunctions (in ALS). - Methods In total, 36 non-symptomatic mutation carriers from ALS or FTD families were examined, including 21 subjects with C9orf72 and 15 with SOD1 mutations. Data were compared with 91 age-matched, education-matched and gender-matched healthy subjects (56 were first-degree relatives from ALS or FTD families, 35 with no known family history of ALS/FTD). MRI scanning for diffusion tensor imaging was performed to map fractional anisotropy (FA). Subjects performed an extensive neuropsychological assessment to address verbal fluency, language, executive, memory and visuospatial function. Measurements were repeated after 12 months. - Results C9orf72 expansion carriers performed significantly worse in verbal fluency and non-verbal memory and presented with distinct alterations in structural white matter integrity indicated by lower FA values in inferior and orbitofrontal cortical areas compared with carriers of SOD1 mutations or healthy subjects. Loss of structural integrity was associated with decreased verbal fluency performance. White matter alterations and cognitive performance showed no changes over 12 months in all subjects. - Discussion Reduced verbal fluency performance seems to be a distinct clinical feature of C9orf72 carriers before symptomatic disease onset without evidence for change over time in our cohort. The results support the emerging hypothesis of a general disorder in development in addition to neurodegeneration in C9orf72 carriers.